SOCIAL CONCERNS DEPICTED IN THE NOVEL "SUNFLOWERS OF DARKNESS" BY KRISHNA SOBTI - Devi, khuraizam Uma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The novel "Sunflowers of Darkness" written by the famous writer Krishna Sobtiji highlights the social concerns. This novel is presented on the problem of ’Ratti’ based on rape in childhood. In this novel, the writer has also portrayed the mental state of the rape victim ’Ratti’ very well, which is not original even if the memory wants to. She keeps getting humiliated in front of her friends by doubling up again and again in the photoshoot event. In this situation, ’Ratti’ is filled with the eagerness to take revenge from each one. We cannot remember that incident in any form. As a result of that incident, she always has the thought of taking revenge from the male race in her mind. So she invites many men to take a change and tries to maintain relations with them but due to no warmth in her body many men cheat her. Due to Ratti’s body being cold or frigid she is named ’Frigidity’. Finally Diwakar gets the right to propose marriage to Ratti. Ratti is a reclusive woman in the Sanatani scriptures. But inside she is much stronger, fearless and brave. Ratti has nothing but bitter memories. The article says that the actor Ratti is not a prostitute, but she has an idea of ​​taking revenge from the male race for an incident in her childhood. The same problem is presented in this novel.